Cost‐effectiveness of left ventricular assist devices as destination therapy in the United Kingdom - Schueler, Stephan (ESC Heart Fail, 2021)
AIMS: Continuous‐flow left ventricular assist devices (LVADs) as destination therapy (DT) are a recommended treatment by National Institute for Health and Care Excellence England for end‐stage heart failure patients ineligible for cardiac transplantation. Despite the fact that DT is frequently used as an LVAD indication across other major European countries and the United States, with consistent improvements in quality‐of‐life and longevity, National Health Service (NHS) England does not currently fund DT, mainly due to concerns over cost‐effectiveness. On the basis of the recently published ENDURANCE Supplemental Trial studying DT patients, we assessed for the first time the cost‐effectiveness of DT LVADs compared with medical management (MM) in the NHS England. METHODS AND RESULTS: We developed a Markov multiple‐state economic model using NHS cost data. LVAD survival and adverse event rates were derived from the ENDURANCE Supplemental Trial. MM survival was based on Seattle Heart Failure Model estimates in the absence of contemporary clinical trials for this population. Incremental cost‐effectiveness ratios (ICERs) were calculated over a lifetime horizon. A discount rate of 3.5% per year was applied to costs and benefits. Deterministic ICER was £46 207 per quality‐adjusted life year (QALY). Costs and utilities were £204 022 and 3.27 QALYs for the LVAD arm vs. £77 790 and 0.54 QALYs for the MM arm. Sensitivity analyses confirmed robustness of the primary analysis. CONCLUSIONS: The implantation of the HeartWare™ HVAD™ System in patients ineligible for cardiac transplantation as DT is a cost‐effective therapy in the NHS England healthcare system under the end‐of‐life willingness‐to‐pay threshold of £50 000/QALY, which applies for VAD patients.